(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Wrist ganglion cysts are the most common soft tissue swellings of the hand and wrist. Although benign, they often cause pain, cosmetic concern, and functional limitation. Various treatment modalities exist, ranging from observation to surgical excision. Minimally invasive techniques such as aspiration with or without adjunctive agents have gained interest due to lower morbidity and ease of performance. Autologous blood instillation after aspiration has been proposed to reduce recurrence by promoting fibrosis and obliteration of the cyst cavity. Aim: To evaluate the effectiveness of aspiration followed by autologous blood instillation in the management of dorsal wrist ganglions in terms of resolution rate, recurrence, and complications. Materials and Methods: This was a prospective interventional study conducted in the Department of General Surgery, Bankura Sammilani Medical College and Hospital over a period of 12 months. The study included patients presenting with clinically diagnosed wrist ganglion cysts attending the outpatient department. A total of 100 patients were enrolled as the study population, who underwent aspiration followed by autologous blood instillation and were subsequently evaluated for outcomes including symptom relief, resolution, and recurrence. Results: In this study of 100 patients, the most common location of wrist ganglion was the dorsal wrist in 78 patients (78%). The volar wrist was involved in 18 patients (18%), while other sites such as tendon sheath were seen in 4 patients (4%). Conclusion: Aspiration with autologous blood instillation is a minimally invasive, safe, and economical option for the treatment of wrist ganglions. It may reduce recurrence rates compared to aspiration alone, though long-term comparative studies are required to establish its definitive role.